Shelf-based scarcity as a cue of luxuriousness: an application of psychophysiology. (25th September 2020) - Sung, Billy; Hatton-Jones, Siobhan; Teah, Min; Cheah, Isaac; Phau, Ian
Abstract : Purpose: The purpose of this paper is to examine the perception of luxuriousness as a novel underlying mechanism of the shelf-based scarcity effect by using both psychophysiological measures (Study 1) and self-reported measures (Study 2). Design/methodology/approach: Two within-subject experimental designs were conducted to examine the effects of low, medium and high stock depletion levels (i.e. shelf-based scarcity) on consumer responses. In Study 1, facial expression analysis was used to examine consumers' liking, and left frontal asymmetry brainwaves were used to examine consumers' approach motivation as a proxy for purchase intention. Study 2 extended the findings with self-reported measures. Findings: In Study 1, perceived product luxuriousness was found to underlie the shelf-based scarcity effect on facial expressions and left frontal asymmetry brainwaves after controlling for other previously proposed mediators (i.e. product popularity and quality). The shelf-based scarcity effect is only observed between low vs high stock levels, whereas moderate stock level depletion does not evoke the shelf-based scarcity effect. Study 2 used self-reported measures to replicate the effect of shelf-based scarcity on product luxuriousness. However, the findings demonstrated the limitation of self-reported measures to identify a significant spill-over effect of perceived luxuriousness to attitude. Research limitations/implications: Extending previous literature that relied heavily on self-reported measures, the current research used psychophysiological methods to uncover perceived luxuriousness as a novel underlying mechanism for the shelf-based scarcity effect. Thus, the findings are not only the first to provide psychophysiological evidence of the shelf-based scarcity effect but also to validate perceived luxuriousness as an underlying mechanism of the shelf-based scarcity effect. Practical implications: The current findings suggest that the shelf-based scarcity effect is only evoked by high (instead of moderate) levels of stock depletion. The study also shows that shelf-based scarcity does not necessarily signal product popularity, but instead it may serve as a cue of product luxuriousness. Adding to other manipulations of retail spaces that elicit luxury perception (e.g. artwork, sensory delight and themed store atmospherics), this implies that businesses are able to use shelf-based scarcity as a cue to enhance or complement the luxury image or the perception of the brand or product. Originality/value: The current research is the first study to use psychophysiological techniques to examine perceived luxuriousness as an underlying mechanism of shelf-based scarcity. It also demonstrates that self-report measures are not sensitive to such an effect in comparison to psychophysiological techniques, explaining why perceived luxuriousness has not been previously found to be an underlying mechanism of shelf-based scarcity.